Analecta Miridologica: Einige nomenklatorische Berichtigungen für die paläarktische Fauna (Hemiptera: Heteroptera). - Carvalho, José Candido de Melo (Contributions to Entomology = Beiträge zur Entomologie, 1955)
Nomenclatural Acts halimocnemis Becker, 1864 (Capsus), stat. n. now a valid taxon linearis Fuessly, 1775 (Cimex), nom. praeocc. by Cimex linearis Fabricius, 1775; now Megalocerea recticornis (Geoffroy, 1787) californicus Van Duzee, 1917 (Excentricus), syn. n. of Ranzovius moerens Reuter, 1905 mexicanus Van Duzee, 1917 (Excentricus), syn. n. of Ranzovius moerens Reuter, 1905 scriptus Fabricius, 1803 (Lygaeus), nom. praeocc. by Lygaeus scriptus Fabricius, 1784; now Brachycoleus decolor Reuter, 1887 punctipennis Reuter, 1879 (Malthacosoma), syn. n. of Capsus halimocnemis Becker, 1864 Excentricorus Carvalho, 1955 (Miridae), gen. n. Platytomatocoris Reuter, 1883 (Miridae), syn. n. of Excentricus Reuter, 1878 bicolor Mulsant & Rey, 1852 (Psallus), nom. praeocc. by Capsus bicolor Le Peletier & Serville, 1825 wagneri Carvalho, 1955 (Sthenarus), nom. n. pro Psallus bicolor Mulsant & Rey, 1852, nec Le Peletier & Serville, 1825